When Worlds Collide : Hunter-Gatherer World-System Change in the 19th Century Canadian Arctic - Friesen, T. Max, 1961- (Book collections on Project MUSE., 2013)
Interactions between societies are among the most powerful forces in human history. However, because they are difficult to reconstruct from archaeological data, they have often been overlooked and understudied by archaeologists. This is particularly true for hunter-gatherer societies, which are frequently seen as adapting to local conditions rather than developing in the context of large-scale networks. This book presents a model for discerning interaction networks based on the archaeological record, and then applies the model to long-term change in an Arctic society. The author has adapted and expanded world-system theory in order to develop a model that explains how hunter-gatherer interaction networks, or world-systems, are structured - and why they change. He has utilized this model to better understand the development of Inuvialuit society in the western Canadian Arctic over a 500-year span, from the pre-contact period to the early twentieth century. As the author combines local archaeological data with more extensive ethnographic and archaeological evidence from the surrounding region, a picture emerges of a dynamic Inuvialuit world-system characterized by bounded territories, trade, warfare, and other forms of interaction. This world-system gradually intensified as the impacts of Euroamerican colonial activities increased. This intensification, the author suggests, was based on pre-existing Inuvialuit social and economic structures rather than on patterns imposed from outside. Ultimately, this intense interacting network collapsed near the end of the nineteenth century. This book offers a new way to comprehend small-scale world-systems from the point of view of indigenous people. Its approach will prove valuable for understanding hunter-gatherer societies around the globe. -- Publisher's website.